Barnum Brown : dinosaur hunter - Sheldon, David (New York : Walker & Co. : Distributed to the trade by Holtzbrinck Publishers, 2006)
An illustrated biography of early twentieth-century paleontologist, Barnum Brown, the man who is credited with first discovering the bones of the Tyrannosaurus Rex.
Includes bibliographical references.
Kirkus Review
3.9
K-3
K-3
Keywords: Brown, Barnum -- Juvenile literature; Brown, Barnum; Brown, Barnum; Dinosaurs -- Juvenile literature; Paleontologists -- United States -- Biography -- Juvenile literature; Dinosaurs; Paleontologists; Dinosaurs; Paleontologists -- Biography